Best practices for describing, consuming, and discovering web services: A comprehensive toolset - Rodriguez, Juan Manuel (2013)
The Service-Oriented Computing (SOC) paradigm has recently gained a lot of attention in the software industry, since SOC represents a novel and a fresh way of architecting distributed applications. SOC is usually materialized via Web Services, which allows developers to structure applications exposing a clear, public interface to their capabilities. Although conceptually and technologically mature, SOC still lacks adequate development support from a methodological point of view. In this paper, we present the EasySOC project, a set of guidelines to simplify the development of service-oriented applications and services. EasySOC is a synthesized catalog of best SOC development practices that arises as a result of several years of research in fundamental Services Computing topics, i.e. WSDL-based technical specification, Web Service discovery, and Web Service outsourcing. In addition, we describe a materialization of the guidelines for the Java language, which has been implemented as a plug-in for the Eclipse IDE. We believe that both the practical nature of the guidelines and the availability of this software that enforces them may help software practitioners to rapidly exploit our ideas for building real SOC applications.